Kinerja Akustik dan Mekanik Panel Sandwich Berbasis Ampas Tebu dan Bambu: Dian Yulia Sari, Aris Minardi, Restu Kristiani, Iwan Yahya, Harjana - Dian Yulia Sari, Dian Yulia Sari; Aris Minardi, Aris Minardi; Restu Kristiani, Restu Kristiani; Iwan Yahya, Iwan Yahya; Harjana, Harjana (Jurnal Fisika dan Aplikasinya, 2025)
Sound absorption performance and mechanical performance have been conducted in panel sandwich based bagasse and bamboo. The testing acoustic performance was conducted experimentally refer to ASTM E-1050-98 standard procedure and mechanical performance using a material testing machine. In this research, thickness variation bagasse composite and bamboo effect of adding a layer on the surface of the upper and lower composite bagasse. The results showed that the influence of the thickness of the sample is to shift the effective sound absorption at low frequencies while adding a layer of bamboo composite bagasse impairment affects the sound absorption coefficient due to a high degree of hardness and low porosity of the lining of bamboo. The effect of thickness on the mechanical performance is to lower the value of MOR and MOE while the effect of adding a layer of bamboo create value MOR MOE values rise and fall. The influence of the layer thickness and the addition of bamboo also change the value of the density of the sample.